Analisis Kemampuan Pemahaman Matematis Ditinjau dari Self-Regulated Learning - Jusra, Hella; Liddini, Uswatun Hasanah (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
The purpose of this study is to analyze the ability of mathematical understanding in terms of Self-Regulated Learning. This is based on students who have not been able to independently identify, recognize, detail and arrange several questions that will arise in the problem. This research is a qualitative research with a descriptive approach, the subjects in this study were students of class X SMA Negeri in Jakarta. Based on the results of research that has been done, it is stated that students have three categories of Self-Regulated Learning, namely high, medium and low. Each question states an indicator of mathematical understanding ability, but only the high Self-Regulated Learning category fulfills all indicators of mathematical understanding ability. Because subjects with high Self-Regulated Learning category can understand all the questions that have been asked. Meanwhile, for students in the moderate Self-Regulated Learning category, they fulfill two indicators, namely; (1) students can define a concept in writing, (2) students can present a concept in a problem and turn it into another form of expression. For the low Self-Regulated Learning category, students do not meet two indicators of mathematical understanding ability, only meet one indicator, namely; can identify problems and determine the outcome of a problem.